Investigation on the occupational situation of clinical research associates in China - Can Du; Qi Han; Ziqian Lu; Jia Li (Frontiers in Medicine)
Clinical research associates (CRAs) are the sponsor’s representatives, monitor the process and quality of clinical trials, their professional quality can affect the quality of clinical trials. But there is a conflict between the large number of CRAs personnel and unsatisfactory quality of clinical trial monitoring, and the reason is unknown. Therefore, our study investigated the occupational status of CRAs through a questionnaire survey. A total of 401 eligible questionnaires were included in the final analysis. Of whom, 71.32% were females, the average age is 27.86 years (range: 22–46 years), 95.01% had a bachelor’s degree or above, and 60% had a pharmaceutical major. 76.31% had month income of <20,000 Yuan RMB, and dissatisfied with their current salary level. Over 80% weekly working time more than 40 h. 79.3% CRAs traveling for less than 7 days per month under the impact of the COVID-19 epidemic. 80% of them are satisfied with promotion channels and company training. Furthermore, Through the analysis of satisfaction differences, we found that CRAs with different educational backgrounds have significant differences in career satisfaction. It was suggested by more than 80% CRAs that the application materials for clinical trials should be unified nationwide and an ethical mutual recognition system. In conclusion, our study is the first large-scale survey of CRAs in China, the current professional situation of CRAs is considerable, but overall it still needs further improvement and enhancement, the monitoring difficulties faced by CRAs mainly come from hospitals, companies, and themselves. With the robust growth of clinical trials in China, hospitals and companies need to improve the professional quality and status of CRAs through a series of measures, further driving the improvement of clinical trial quality.